Community Based Disaster Management in Indonesia - Chatarina Muryani (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this article writing is to describe and analyze how the implementation of Community Based Disaster Management in Indonesia. This Sources of articles writing were various libraries, including books, journals, regulations and articles on the website. From the literature review, it can be concluded that CBDM has an important role in disaster risk reduction both in Indonesia and in other countries, and CBDM in Indonesia has been implemented but there are still problems:  overlapping management, guidance for sustainability and funding.